Changes In Red Tilapia (Oreochromis Sp.) Mouth Mucus During Mouthbrooding: A Proteomics Approach - Koe , Chun Iq (2010)

(untitled)
Red tilapia (Oreochromis sp.) is a maternal mouthbrooder displaying an advanced form of parental care by keeping the eggs/fries inside the mouth. Proteomics approach was used to investigate the changes of the proteome in the mouth mucus during mouthbrooding. Non-parental mouth mucus proteome was used as control. With PMF and MS/MS, a total of 25 protein spots were confidently identified. The identified proteins such as glycolytic enzymes, type II keratin, HSC70, proteasome, and NKEF suggests that there is a need for higher energy production, stress mediation, protein maintenance, and specific defence mechanism in parental tilapia during mouthbrooding. In summary, proteomics approach has revealed that there are changes in the tilapia mouth mucus proteome during mouthbrooding and the identified proteins provide interesting insights in mouth mucus proteome.